Pengaruh Perempelan terhadap Produksi Tanaman Cabai Merah Besar (Capsicum annum L. ) - Muafi, Futuh; Mei Arini, Silvia Fitri (Program Studi Agroteknologi, 2021)
Increasing of Chili production can be apply with various of methodologies one of them by giving treatment to chili crop. Among of general practice treatment done by several of farmer is using waters bud sealing growth in chili crop leaf axillary. Sealing is the effort or removal activity of waters bud which growth from leafs axillary. This bud is not productive and will distrubes absolute growth. Therefore, lateral bud ough to seal and removal. The aim of this research to investigate the effectiveness of sealing red chili crop (Capsicum annum L.) production, and to identfy the effect of the big red chili (Capsicum annum L.) quality. This research carried out on february- june 2018 at Krajan, Ampel, Wuluhan, Jember, Jawa Timur. This research occur during 4 month begind on february - june 2018, totally consist of four treatments one control by three times of examined, in each treatment AO= Sealing as Control 0%, Al= 25% Sealing, A2= Sealing 50%, A3= Sealing 75%, A4= Sealing 100%. This testing conducted by F- test is using variant analysing (ANOVA) if occur the signficant effect it will continue with 5% Duncan test. Based on ANOVA test that has been done that sealing concern on big red chili crop is not obvious on the effect of observation parameter for instance (high of plant, fruit weigh, amount of fruit, longevity of flowering) and has the obvious effect observation parameter of harvesting longevity.